Association of Testosterone Therapy With Risk of Venous Thromboembolism Among Men With and Without Hypogonadism - Walker, Rob F. (JAMA Intern Med, 2019)
IMPORTANCE: Testosterone therapy is increasingly prescribed in patients without a diagnosis of hypogonadism. This therapy may be associated with increased risk of venous thromboembolism (VTE) through several mechanisms, including elevated hematocrit levels, which increase blood viscosity. OBJECTIVE: To assess whether short-term testosterone therapy exposure is associated with increased short-term risk of VTE in men with and without evidence of hypogonadism. DESIGN, SETTING, AND PARTICIPANTS: This case-crossover study analyzed data on 39 622 men from the IBM MarketScan Commercial Claims and Encounter Database and the Medicare Supplemental Database from January 1, 2011, to December 31, 2017, with 12 months of follow-up. Men with VTE cases who were free of cancer at baseline and had 12 months of continuous enrollment before the VTE event were identified by International Classification of Diseases codes. Men in the case period were matched with themselves in the control period. Case periods of 6 months, 3 months, and 1 month before the VTE events were defined, with equivalent control periods (6 months, 3 months, and 1 month) in the 6 months before the case period. EXPOSURES: National drug codes were used to identify billed testosterone therapy prescriptions in the case period (0-6 months before the VTE) and the control period (6-12 months before the VTE). MAIN OUTCOMES AND MEASURES: The main outcome in this case-only experiment was first VTE event stratified by the presence or absence of hypogonadism. RESULTS: A total of 39 622 men (mean [SD] age, 57.4 [14.2] years) were enrolled in the study, and 3110 men (7.8%) had evidence of hypogonadism. In age-adjusted models, testosterone therapy use in all case periods was associated with a higher risk of VTE in men with (odds ratio [OR], 2.32; 95% CI, 1.97-2.74) and without (OR, 2.02; 95% CI, 1.47-2.77) hypogonadism. Among men without hypogonadism, the point estimate for testosterone therapy and VTE risk in the 3-month case period was higher for men younger than 65 years (OR, 2.99; 95% CI, 1.91-4.68) than for older men (OR, 1.68; 95% CI, 0.90-3.14), although this interaction was not statistically significant (P = .14). CONCLUSIONS AND RELEVANCE: Testosterone therapy was associated with an increase in short-term risk for VTE among men with and without hypogonadism, with some evidence that the association was more pronounced among younger men. These findings suggest that caution should be used when prescribing testosterone therapy.